LEGAL IMPLICATIONS OF POJK No. 22/2023 ON THE CREDIT COLLECTION PROCESS BY POJK IN INDONESIA - Tarigan, Ngueken; Harjono, Dhaniswara K.; Betlehn, Andrew (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This is where the financing company (leasing) manages the purchase of motor vehicles on credit. The financing company (leasing) is tasked with making a credit agreement containing payment provisions, interest, late fines, tenor, and default clauses. Also, each vehicle is registered as a fiduciary guarantee which is civilly a unit when the payment has not been paid in full by the debtor, the motorcycle unit is an object of fiduciary guarantee controlled by the creditor (leasing) The approach method used in this study uses a juridical-empirical approach. The juridical approach is used to analyze various laws and regulations governing credit. While the empirical approach is used to analyze law as a rule that is not merely normative, but law can see in the lives of people who always interact and relate to aspects of community life. The meeting of these two interests is what can make cession can be used as an alternative solution to solving problematic credit where each party will equally benefit whether from the debtor, creditor or cessionary side. The cessionary has a very important role where when the cessionary can bring together the interests of the old creditors and the debtor, the problematic credit can be resolved easily. As a new creditor, the cessionary can mediate with the debtor to find a middle ground for resolving the problem of bad credit.